2018
DOI: 10.3390/biom8030097
|View full text |Cite
|
Sign up to set email alerts
|

α-Tocopheryl Succinate-Based Polymeric Nanoparticles for the Treatment of Head and Neck Squamous Cell Carcinoma

Abstract: The aim of this work is to study, in an in vitro head and neck squamous cell carcinomas model the anti-angiogenic and anti-migratory properties of self-assembled polymeric nanoparticles (NPs) with demonstrated selective anticancer activity. The NPs are based on α-tocopheryl succinate (α-TOS) encapsulated in the hydrophobic core of the NPs. We analyzed the effect of the newly synthetized α-TOS-loaded NPs in proliferating endothelial cells and hypopharynx carcinoma squamous cells and measured markers of angiogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Nanomedicine is an emerging form of treatment that is dedicated to alternative drug delivery and improved therapeutic efficacy, while reducing harmful side Oxidative Medicine and Cellular Longevity effects on normal tissues. New nanoparticle systems with highly flexible and rapid drug design and production capabilities can be created, which can be designed based on the genetic characteristics of tumors; therefore, making the drug selection for individual patient treatment and overcoming multiple forms of multidrug resistance look promising and open up new prospects for cancer treatment [262][263][264][265][266][267][268]. The effect of metal nanoparticles on ROS concentration has been shown to play a role in both radiosensitization and radioprotection.…”
Section: Application Of the Nanoparticle System Based On Rosmentioning
confidence: 99%
“…Nanomedicine is an emerging form of treatment that is dedicated to alternative drug delivery and improved therapeutic efficacy, while reducing harmful side Oxidative Medicine and Cellular Longevity effects on normal tissues. New nanoparticle systems with highly flexible and rapid drug design and production capabilities can be created, which can be designed based on the genetic characteristics of tumors; therefore, making the drug selection for individual patient treatment and overcoming multiple forms of multidrug resistance look promising and open up new prospects for cancer treatment [262][263][264][265][266][267][268]. The effect of metal nanoparticles on ROS concentration has been shown to play a role in both radiosensitization and radioprotection.…”
Section: Application Of the Nanoparticle System Based On Rosmentioning
confidence: 99%
“…Another study revealed that δ-tocotrienol exhibited potential against both melanoma and its associated stem cells [228,229], while displaying suppressive action on prostate cancer stem-like cells [230]. Recent findings also indicated that tocotrienols displayed antiangiogenic protein expression of VEGF in colorectal cancer [231], malignant mesothelioma [232], breast cancer [233], ovarian carcinoma [234], and head and neck squamous cell carcinoma [235]. All these studies provide ample evidence of the role of tocotrienol in arresting tumour growth by inhibiting angiogenesis.…”
Section: Anti-angiogenesismentioning
confidence: 99%
“…Shiozawa et al, have also elegantly illustrated the cytotoxic effect of redox-silent analogue of tocotrienol in inhibiting survival of PC3 cells (androgen-independent prostate cancer (PCa) cell line) under hypoxia, through inhibition of Fyn/HIF-1α signaling cascade, which may lead to the establishment of a new effective therapy for PCa [87]. In addition, pre-clinical data from numerous other studies have also reported that γ-T3 alleviates angiogenic protein expression (VEGF) in colorectal cancer [88], malignant mesothelioma [89], breast cancer [90], ovarian carcinoma [91], head and neck squamous cell carcinomas [92], and other cancers. Thus, in view of the above scientific reports, tocotrienols appear to be important therapeutic molecules for improvement of prognosis in cancer patients by targeting angiogenesis.…”
Section: Major Anti-cancer Functions Of Tocotrienolsmentioning
confidence: 99%